1983
DOI: 10.1007/bf00027429
|View full text |Cite
|
Sign up to set email alerts
|

Rotifers as indicators of water quality

Abstract: Six hundred and twenty species and lower taxonomical units of Rotatoria found in Czechoslovakia and surrounding countries are listed alphabetically and classified according to water quality. The numerical characteristics include the saprobic valence in 10 balls, the indicative weight of species, I i , and the individual saprobic index, S i . Rotifers are considered to be good indicators and some of them are figured on Plates 1-3. The situation is illustrated by four graphs and the relation to BOD 5 values is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
249
2
45

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 418 publications
(314 citation statements)
references
References 53 publications
18
249
2
45
Order By: Relevance
“…It is well known that zooplankton species may not always ideally cope with laboratory conditions, given stress-induced factors interfering with reproductive rates and, thus, density growth ( Sarma and Nandini, 2001). As in the present investigation, several studies also found positive correlations between Brachionus species and eutrophic conditions (Gannon and Stemberger, 1978;Sládeck, 1983;Blancher, 1984;Berzins and Pejler, 1989;Matsumura-Tundisi et al, 1990;Pontin and Langley, 1993;Torres-Orozco and Zanatt, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…It is well known that zooplankton species may not always ideally cope with laboratory conditions, given stress-induced factors interfering with reproductive rates and, thus, density growth ( Sarma and Nandini, 2001). As in the present investigation, several studies also found positive correlations between Brachionus species and eutrophic conditions (Gannon and Stemberger, 1978;Sládeck, 1983;Blancher, 1984;Berzins and Pejler, 1989;Matsumura-Tundisi et al, 1990;Pontin and Langley, 1993;Torres-Orozco and Zanatt, 1998).…”
Section: Discussionsupporting
confidence: 80%
“…5 and 6). Zooplankton, owing to their small, fast reproducing and sensitive characteristics, are good indicators of environmental changes (Sládeček, 1983) and frequently used in environmental monitoring and assessment (Gulati, 1983;Xu et al, 2005;Yang et al, 2009). In the present case, the zooplankton community structure including qualitative and quantitative parameters indicated the different stages well.…”
Section: Discussionmentioning
confidence: 52%
“…Rotifers are usually regarded as bio-indicators of water quality (Sládeček, 1983), and their abundance and population characteristics are used as effective indicators of environmental changes (Attayde and Bozelli, 1998). According to the results, Factor-1 and Factor-2 were both mainly associated with rotifers, and Factor-4 mainly with zooplanktonic crustaceans, while PCA showed that Factor-1 was mainly affected by IP, Chl-a and TP, Factor-2 by EC, TDS and TN, and Factor-4 by SD, water depth and temperature.…”
Section: Community Structure Variationmentioning
confidence: 99%